Halal Label vs Product Quality in Halal Cosmetic Purchasing Decisions - Anggadwita, Grisna; Alamanda, Dini Turipanam; Ramadani, Veland (IKONOMIKA, 2019)
The purpose of this study was to analyze cosmetics purchasing decisions by consumers with consideration of halal labels or product quality where brand image as an intervening variable. This study uses quantitative methods with confirmatory objectives. Questionnaires are distributed using a purposive sampling method for 400 respondents in several villages throughout Indonesia. The results showed that the halal label significantly influenced brand image and purchasing decisions. Product quality affects brand image but has no impact on purchasing decisions. Meanwhile, brand image has a significant influence on purchasing decisions.  The research implications show that for rural communities, promotion of halal cosmetics is more useful for driving purchasing decisions compared to the quality of cosmetic products.